Sand Deposit Control Strategy on Centrifugal Pump Type Overhung 4 Size 4x11 Using API 682 Piping Plan 13 - Malik, Miftahul Fahrizal Nur; Hidayati, Noor; kamal, Dianta Mustofa (Journal of Energy, Material, and Instrumentation Technology, 2025)
Centrifugal pumps type Overhung 4 size 4x11 often experience sand deposits and erosion problems, especially in the oil and gas industry, resulting in reduced productivity and increased repair costs. This study evaluates the application of the Piping Plan 13 API 682 as a solution to this problem. The 5-Why Analysis method is used to identify the root cause of sand deposits, which were associated with sand contamination from a liquid source and the absence of an effective filtering system. The implementation of Piping Plan 13 aims to prevent sand deposits in critical areas, such as the Pedestal Cover and Pedestals, by leveraging the circulation design of the pipeline. The results showed a 19.75% increase in pump productivity and a 76.12% reduction in repair costs. Productivity increases reached 336,000 barrels (about 53,419,731 liters) over 16 days of operation, while the repair cost fell from Rp6,699,950 to Rp1,600,000. These findings indicate that Piping Plan 13 API 682 is an effective solution to increase the life and performance of the centrifugal pump and reduce maintenance costs in operating conditions with high sand contamination.